FORMATION OF HEALTHY THINKING IN STUDENTS BASED ON THE WORKS OF A. AVLONI (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The development of healthy thinking in students is a fundamental goal of education, essential for fostering critical reasoning, ethical decision-making, and social awareness. Abdulla Avloni’s works emphasize the importance of intellectual independence, moral integrity, and national consciousness in shaping an enlightened generation. His writings serve as a guide for modern pedagogy, advocating for an education system that nurtures analytical skills, ethical values, and civic engagement. By integrating Avloni’s principles into contemporary education, educators can cultivate responsible and critically thinking individuals capable of contributing to societal progress.